Elevated Mitral Valve Pressure Gradient Is Predictive of Long‐Term Outcome After Percutaneous Edge‐to‐Edge Mitral Valve Repair in Patients With Degenerative Mitral Regurgitation (MR), But Not in Functional MR - Patzelt, Johannes (John Wiley and Sons Inc., 2019)

(untitled) (J Am Heart Assoc)
BACKGROUND: This study analyzed the effects on long‐term outcome of residual mitral regurgitation (MR) and mean mitral valve pressure gradient (MVPG) after percutaneous edge‐to‐edge mitral valve repair using the MitraClip system. METHODS AND RESULTS: Two hundred fifty‐five patients who underwent percutaneous edge‐to‐edge mitral valve repair were analyzed. Kaplan–Meier and Cox regression analyses were performed to evaluate the impact of residual MR and MVPG on clinical outcome. A combined clinical end point (all‐cause mortality, MV surgery, redo procedure, implantation of a left ventricular assist device) was used. After percutaneous edge‐to‐edge mitral valve repair, mean MVPG increased from 1.6±1.0 to 3.1±1.5 mm Hg (P<0.001). Reduction of MR severity to ≤2+ postintervention was achieved in 98.4% of all patients. In the overall patient cohort, residual MR was predictive of the combined end point while elevated MVPG >4.4 mm Hg was not according to Kaplan–Meier and Cox regression analyses. We then analyzed the cohort with degenerative and that with functional MR separately to account for these different entities. In the cohort with degenerative MR, elevated MVPG was associated with increased occurrence of the primary end point, whereas this was not observed in the cohort with functional MR. CONCLUSIONS: MVPG >4.4 mm Hg after MitraClip implantation was predictive of clinical outcome in the patient cohort with degenerative MR. In the patient cohort with functional MR, MVPG >4.4 mm Hg was not associated with increased clinical events.